1997
DOI: 10.1177/026765919701200208
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of gaseous emboli release in five membrane oxygenators

Abstract: The purpose of this study was to compare the air handling capability of five currently used membrane oxygenators: the Avecor Affinity, the Bentley SpiralGold, the Medtronic Maxima Plus, the Sarns Turbo and the Sorin Monolyth M. A circuit was constructed to include a hardshell venous reservoir and roller pump. Pressure monitoring sites and ultrasonic microbubble detection probes were located proximal and distal to the oxygenator. An air injection/infusion site was provided proximal to the roller pump inlet. Eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…17 Although, traditionally, removing gaseous microemboli from the CPB circuit has been assumed by using arterial line filters and improving design of oxygenator and venous reservoir, introduction of air into the venous line still resulted in the detection of gaseous microemboli in the arterial line prior to the arterial cannula, particularly when using vacuum assisted venous drainage during CPB procedure. 6,7 In our simulated neonatal CPB model, the results showed that, regardless of the type of perfusion mode, increasing the pump flow rate and introducing 5 ml air into venous line resulted in more microemboli detected by the EDAC TM system at postpump site; this result was in agreement with Beckley and DeSomer's that higher blood flow rates were associated with a higher release of air, 8,9 because higher flow rates generated higher blood flow velocities, which shorten the contact time between gaseous microemboli and the venous reservoir filter; however, microemboli were rarely detected at postoxygenator site and almost never at postfilter site, which means the majority of microemboli were removed by the oxygenator.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…17 Although, traditionally, removing gaseous microemboli from the CPB circuit has been assumed by using arterial line filters and improving design of oxygenator and venous reservoir, introduction of air into the venous line still resulted in the detection of gaseous microemboli in the arterial line prior to the arterial cannula, particularly when using vacuum assisted venous drainage during CPB procedure. 6,7 In our simulated neonatal CPB model, the results showed that, regardless of the type of perfusion mode, increasing the pump flow rate and introducing 5 ml air into venous line resulted in more microemboli detected by the EDAC TM system at postpump site; this result was in agreement with Beckley and DeSomer's that higher blood flow rates were associated with a higher release of air, 8,9 because higher flow rates generated higher blood flow velocities, which shorten the contact time between gaseous microemboli and the venous reservoir filter; however, microemboli were rarely detected at postoxygenator site and almost never at postfilter site, which means the majority of microemboli were removed by the oxygenator.…”
Section: Discussionsupporting
confidence: 86%
“…[1][2][3] Gaseous microemboli are common during CPB procedure and may be entrained in the extracorporeal circuit or may be introduced into the circuit by ways, such as perfusionist interventions, 4 initiation of CPB, excessive cardiotomy suction, 5 and vacuum-assisted venous drainage. 6,7 Gaseous microemboli may also be generated by circuit components as well, such as oxygenator, 8,9 venous reservoir, 10 or even roller pump. 11 With current Doppler systems, it is possible to detect gaseous microemboli if the size is Ͼ40 m; emboli smaller than 40 m will not be detected.…”
mentioning
confidence: 99%
“…Although others have tried to speculate on what was happening to gas once it had entered the oxygenator, they had no means to measure or quantify it. 7 The technique described in this paper gives the ability to actually measure and quantify the capability of a given device to trap, release or evacuate air. Because of the lack of existing data on bubble dynamics during extracorporeal circulation, we believe that this test protocol should become a standard procedure in combination with pulsed Doppler bubble counting for the evaluation and study of the air removal and air trap capabilities of membrane oxygenators or artificial lungs.…”
Section: Discussionmentioning
confidence: 99%
“…However, membrane oxygenators can vary in their air-handling performances, as has been frequently reported. [4][5][6][7] The assessment of air-handling capabilities of an oxygenator generally includes an ultrasonic bubble counter. 8 However, this method is not sufficiently quantitative and has low reproducibility due to the limitations of the working principle.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygenators are also capable of removing GMBs, although they are not specifically designed for it [13]. The factors favouring GMB-adsorption within the oxygenator are top-to-bottom blood flow in the membrane, lower transmembrane pressure gradient and fibre coating [20]. From these factors, transmembrane pressure gradient seems less effective during PP because of its persistent and wide phasic variations.…”
Section: Discussionmentioning
confidence: 99%